2003
DOI: 10.1007/s11661-003-0281-z
|View full text |Cite
|
Sign up to set email alerts
|

Primary creep behavior of Ti-48Al-2W as a function of stress and lamellar morphology

Abstract: The fully lamellar microstructure of powder metallurgy Ti-48Al-2W after cooling from the ␣ region to 1280°C, followed by air cooling and aging at 950°C for up to 96 hours, is presented. Aging times as short as 5 hours result in acicular-shaped precipitates of W-rich ␤ 0 along lamellar interfaces, with the ␤ 0 size increasing with aging time. The ␤ 0 precipitates nucleate and grow in the ␣ 2 lamellae. Concurrently, with the formation of ␤ 0 , the ␣ 2 decomposes into discontinuous lamellae. Aging to precipitate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
23
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 32 publications
3
23
0
Order By: Relevance
“…In addition, discontinuous a 2 -lamellae contain fine needlelike particles with average width of 25 nm and length of 200 nm, which were identified as B2-phase [13,15]. As reported by Seo et al [16,17], fine B2 precipitates formed at the a 2 /g interfaces before creep testing improve the creep resistance of the alloy by impeding interface dislocation mobility, reducing the generation of g matrix dislocations from lamellae and preventing dislocations from passing through lamellar interfaces. In the case of the ABB-2 alloy, the strengthening effect of the B2 precipitates is enhanced by co-precipitation of fine Ti 5 Si 3 particles along the lamellar interfaces with a similar effect on the dislocation mobility.…”
Section: Resultsmentioning
confidence: 96%
“…In addition, discontinuous a 2 -lamellae contain fine needlelike particles with average width of 25 nm and length of 200 nm, which were identified as B2-phase [13,15]. As reported by Seo et al [16,17], fine B2 precipitates formed at the a 2 /g interfaces before creep testing improve the creep resistance of the alloy by impeding interface dislocation mobility, reducing the generation of g matrix dislocations from lamellae and preventing dislocations from passing through lamellar interfaces. In the case of the ABB-2 alloy, the strengthening effect of the B2 precipitates is enhanced by co-precipitation of fine Ti 5 Si 3 particles along the lamellar interfaces with a similar effect on the dislocation mobility.…”
Section: Resultsmentioning
confidence: 96%
“…1,2 Various microstructures can be obtained through heat treatment, in particular, precipitation-strengthened ␥-TiAl alloys exhibit good elevated-temperature strength and modulus. 3 For many hightemperature structural applications, the allowable total deformation is only about 1%. Since a significant portion of this can occur during primary creep, there is a need for better understanding of this phenomenon.…”
mentioning
confidence: 99%
“…The grain size of the ␥-TiAl was about 150 m. Details of the processing and microstructures of the Ti-48Al-2W alloy used in this study can be found in the literature. 3 Cylindrical tensile specimens, with a nominal gauge diameter of 6.5 mm, were machined for two series of in situ neutron-diffraction measurements using the SMARTS instrument at Los Alamos Neutron Science Center. 5 During the quasistatic tension test, the applied stress was increased incrementally with steps of 20 up to 260 MPa (macroscopic 0.2% yield point) and then with steps of 10 to a maximum load of 435 MPa.…”
mentioning
confidence: 99%
“…It is noticeable that the lamellar structure no longer exists in the diffusion zone as shown in Fig. 10a and b. Seo et al 22 reported that during the aging of PM Ti-48Al-2W alloy at 950uC, the a 2 lamellar became discontinuous as the aging time increased. In this study, the discontinuous a 2 lamellae were also observed in the area below the diffusion zone as shown in Fig.…”
Section: Elemental Distributions On Cross-sectionmentioning
confidence: 94%